Anti-bacterial activity of Oroxylum indicum methanolic leaves extract against gram negative bacteria - Zulkipli, Nur Fatin Julia Nabila (Universiti Sains Malaysia, 2017)
lndicum is used as a traditional remedy of many ailments and its leave extract has been reported to have antimicrobial properties. The purpose of this study was to evaluate the in vitro anti-bacterial activity of the methanolic leaves extract of O. indicum against selected bacteria species. Methanolic leaves extract of O. indicum was tested for anti-bacterial activity against E. coli, S.flexneri, P. mirabilis, P. vulgaris, P. aeruginosa, K. pneumoniae, and S. Typhi. Anti-bacterial activities were evaluated by well-diffusion method and the Minimum Inhibitory Concentration (MIC) was determined using the twofold serial broth microdilution technique of concentration ranging from 150 mg/mL to 1.17 mg/mL. After 24 hours of incubation, the Minimum Bactericidal Concentration (MBC) was determined by sub-culturing the wells which showed no turbidity onto Nutrient agar (NA). The presence of potential secondary metabolites in the crude extract was screened by phytochemical qualitative test. The methanolic leaves extract of O. indicum showed good anti-bacterial activity and P. vulgaris being the most susceptible among the tested bacteria species. The methanolic leaves extract of O. indicum also bactericidal to P. vulgaris and S. flexneri (MBC/MIC ratio of 4.00). Flavonoid, tannin, triterpenoid, and steroid were the major secondary metabolites of the crude extract. The study suggested that O. indicum methanolic leaves extract has promising anti-bacterial activity.